Digitalization in Promoting Women's Empowerment and a Post-Pandemi Creative Economy - Rini Setiawati; Mubasit; Rahmat Hidayat (West Science Journal Economic and Entrepreneurship, 2023)
This article aims to find out what kind of strategy was implemented by the Provincial Government of Lampung in encouraging women to increase MSMEs to the realm of the creative economy during the pandemic and how women from various business sectors are utilizing digital media as digital economic opportunities with their roles as wives and mothers. . To examine this focus, the author uses the theory of women agency which will help explore aspects including resources, agency and achievement. The results of the study found that the efforts of the Lampung Provincial Government to encourage women to become empowered agencies in the creative economy sector bore fruit. Seeing the opportunities for digitalization and the dominance of women in the use of social media, Lampung Province has successfully won the 2020 Kemen-PPPA Parahita Ekapraya Award (APE) because it is considered successful in implementing Gender Mainstreaming (PUG) in women's empowerment programs. In addition, the creative economy helps women to be able to carry out their activities as entrepreneurs without neglecting their role as wives/mothers. However, they must also be able to negotiate domestic and public roles. This research found that successful negotiation rests on an agreement with the husband in managing time, still placing the family as a priority, and positioning the husband as a work partner. The creative economy helps women to be able to carry out their activities as entrepreneurs without neglecting their role as wives/mothers. However, they must also be able to negotiate domestic and public roles. This research found that successful negotiation rests on an agreement with the husband in managing time, still placing the family as a priority, and positioning the husband as a work partner. The creative economy helps women to be able to carry out their activities as entrepreneurs without neglecting their role as wives/mothers. However, they must also be able to negotiate domestic and public roles. This research found that successful negotiation rests on an agreement with the husband in managing time, still placing the family as a priority, and positioning the husband as a work partner.